2001
DOI: 10.1111/j.1439-0434.2001.tb03881.x
|View full text |Cite
|
Sign up to set email alerts
|

Four Spanish Isolates of Pear Decline Phytoplasma are Related to Other European Phytoplasmas of the Apple Proliferation Group *

Abstract: A portion of about 1000 bp within the 16S rDNA of four pear decline (PD) symptomatic trees (two from Badajoz and two from Sevilla) was ampli®ed by nested polymerase chain reaction (PCR) and directly sequenced. A sequence similarity search against the EMBL and GenBank nucleotide databases showed that they were most similar to two previously sequenced isolates of pear decline phytoplasma of German and Italian origin. In a phylogenetic analysis they clustered in a separate branch within the apple proliferation gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the beginning of this study, the phytoplasma-specific rDNA sequence was successfully amplified using PCR with DNA templates prepared from the PDTW-affected pear trees when using the phytoplasma-specific primer pair f1/r1 (Lin & Lin, 1998), but no PCR product was amplified when using the PD phytoplasmaspecific primer pair fPD/rPDS (Lorenz et al, 1995). Since it is known that these primers did not amplify all European strains of the PD agent (Lorenz et al, 1995;Martín et al, 2001), it was not surprising that the PD-specific primer pair fPD/rPDS did not amplify PDTW phytoplasma. In this study, phytoplasma particles were successfully observed by TEM in pears with decline symptoms when using the samples that gave positive PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning of this study, the phytoplasma-specific rDNA sequence was successfully amplified using PCR with DNA templates prepared from the PDTW-affected pear trees when using the phytoplasma-specific primer pair f1/r1 (Lin & Lin, 1998), but no PCR product was amplified when using the PD phytoplasmaspecific primer pair fPD/rPDS (Lorenz et al, 1995). Since it is known that these primers did not amplify all European strains of the PD agent (Lorenz et al, 1995;Martín et al, 2001), it was not surprising that the PD-specific primer pair fPD/rPDS did not amplify PDTW phytoplasma. In this study, phytoplasma particles were successfully observed by TEM in pears with decline symptoms when using the samples that gave positive PCR results.…”
Section: Discussionmentioning
confidence: 99%